The Sum of series 1+2+3+4+5+6…

Build on the basics that you now the sum of series 1-2+3-4+5-6.... we defined as s2 in the previous post.

from this assumption, let’s find the sum of series 1+2+3+4+5+6 ... suppose as s.

s = 1+2 +3+4+5+6...
s-s2 = 1+2+3+4+5+6...-(1-2+3-4+5-6...)
s-s2 = 1+2+3+4+5+6...-1+2-3+4-5+6...
s-s2 = 0+4+0+8+0+12+0+16...
s-s2 = 4(1+2+3+4+5+6...)
s-s2=4s
s-1/4=4s
-1/4=3s
s = -1/12

so, 1+2+3+4+5+6... series s = -1/12

what!? you don’t agree? Me too!

Similar Posts

Leave a Reply

Your email address will not be published.